Chest pain, troponin rise, and ST-elevation in an adolescent boy following the use of the synthetic cannabis product K2 - Zaleta, Sona (Ann Pediatr Cardiol, 2016)
“Legal highs” such as K2, which typically contain synthetic cannabinoids, are increasingly popular with adolescents around the world. We have limited knowledge concerning their toxicity or adverse effects and their mechanism of action is poorly understood. While synthetic cannabinoids have been linked to adverse cardiovascular effects, cases of ST-elevation myocardial infarction (STEMI) associated with K2 use are exceedingly rare. We report a case of a 14-year-old boy who suffered an STEMI after smoking K2. To our knowledge, this is not only the youngest case of an STEMI associated with K2 use, but also the first case to be reported outside of the United States of America. Pediatricians worldwide must be aware of the clinical significance and potential harm associated with the use of synthetic cannabinoids, to better educate patients and their families regarding the dangers of using such “legal” substances.